Effect of Aqueous Extract of Moringa oleifera Leaves on Hematological and Biochemical Parameters in Broilers (Cobb 500) - Ousmane, ssa Abdel Djalil; Mouchili, Mama; Oumar, Moucthar Kodbe; Choupou, Taling Princesse Aicha; Miegoue, Emile; Lemoufouet, Jules; Tendonkeng, Fernand (International Journal of Poultry Science, 2025)
Objective: This study was designed to evaluate the effect of the aqueous extract of Moringa oleifera leaves on the hematological and biochemical parameters of broilers. Materials and Methods: The study was conducted at T3F Poultry Farm, Makong from February to April 2024. A total of 150 day-old chicks of Cobb 500 strain, with an average weight of 40.09±3 g, were randomly divided into 20 experimental units according to a completely randomized design with 4 replicates of 7 to 8 subjects each for a period of seven weeks. The experimental rations were formulated such that the aqueous extract of Moringa oleifera leaf was included in the diet at 0 g (R0), 0.25 g (R1), 0.50 g (R2), 0.75 g (R3) and 1 g (R4) both at the beginning and at the end of the study. R0 served as the control ration. Results: The main results showed that the addition of Moringa oleifera leaf extracts in the diet had no significant effect on mean platelet volume levels. On the other hand, mean corpuscular volume, hematocrit and hemoglobin levels increased with increasing levels of Moringa oleifera leaf extract in the diet, while platelet levels decreased with increasing levels of extract. The HDL cholesterol, triglycerides, ALT and AST decreased with the inclusion of aqueous extract of Moringa oleifera leaves in the diet. The addition of aqueous extracts of Moringa oleifera leaves to the diet had no significant effect on total protein, albumin, globulins, total cholesterol, glucose, creatinine and urea. Conclusion: Meat with fewer bacterial residues was obtained when Moringa oleifera leaf extracts were included in the diet, which is beneficial for health-conscious consumers.